PERAYAAN EKARISTI UNTUK TRADISI BALALA DARI SUKU DAYAK BANYADU - Herwindo Chandra (Jurnal Filsafat dan Teologi Katolik, 2020)
This paper outlines the Balala Tradition which is one of the Dayak Banyadu tribe traditions. The Catholic Church values the culture and values of the local wisdom of its people. However, inculturation of culture into a celebration of faith requires a method approach. Models of faith contextualization from Stevan Bevan are one of the methods used in this paper. Identification of the problem of the Belala Tradition is the weak signification of the faith of the Dayak Banyadu tribe who are Catholic in living the Belala Tradition. So the focus of this paper is on the inculturation of the Balala Tradition in the Catholic faith paradigm. The purpose of this study is to provide a theological basis and meaning of the Catholic faith for the value of locality in the Belala Tradition. This paper will explore the experience of the existence of the Dayak Banyadu tribe in living this tradition in the eyes of the Catholic faith.